1967
DOI: 10.1113/jphysiol.1967.sp008142
|View full text |Cite
|
Sign up to set email alerts
|

The reflex effects of alterations in lung volume on systemic vascular resistance in the dog

Abstract: SUMMARY1. The reflex effects of alterations in lung volume on systemic vascular resistance have been studied in anaesthetized dogs under conditions in which the systemic circulation was perfused at constant blood flow. The pressures in the isolated perfused carotid sinuses and aortic arch, and the arterial blood Po2 and Pco2 were maintained constant.2. A maintained inflation of the lungs produced by injection of air into the trachea caused a fall in systemic arterial perfusion pressure, indicating vasodilatati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
1

Year Published

1969
1969
2002
2002

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 37 publications
(30 reference statements)
9
59
1
Order By: Relevance
“…5, and it shows that the effects on the cardiovascular system produced by inflation of the lungs were markedly lessened by interruption of the vagus nerves. DISCUSSION Partly in confirmation of previous findings (6,7) the results of the present investigation clearly indicate that pulmonary stretch receptors do affect cardiovascular function, and that their activation results in reflex inhibition of sympathetic tone with consequent decreases in myocardial performance, heart rate, and peripheral vascular resistance. That these observed depressor responses are indeed reflex in nature rather than the result of mechanical effects produced by inflation of the lungs is indicated by the fact that they were observed in animals on right heart bypass, which means that they were not merely the result of induced changes in venous return, since blood flow into the pulmonary artery was kept constant.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…5, and it shows that the effects on the cardiovascular system produced by inflation of the lungs were markedly lessened by interruption of the vagus nerves. DISCUSSION Partly in confirmation of previous findings (6,7) the results of the present investigation clearly indicate that pulmonary stretch receptors do affect cardiovascular function, and that their activation results in reflex inhibition of sympathetic tone with consequent decreases in myocardial performance, heart rate, and peripheral vascular resistance. That these observed depressor responses are indeed reflex in nature rather than the result of mechanical effects produced by inflation of the lungs is indicated by the fact that they were observed in animals on right heart bypass, which means that they were not merely the result of induced changes in venous return, since blood flow into the pulmonary artery was kept constant.…”
Section: Resultssupporting
confidence: 79%
“…Thus, the baroreceptors were undoubtedly stimulated by the intervention and the sympathetic nervous activity that was measured was probably the resultant effect of the balance between the -baroreceptor reflex and the pulmonary stretch reflex. That such a balance does indeed exist is substantiated by the findings of Daly and coworkers who observed that the magnitude of vasodepression produced by inflation of the lungs was related to the pressures within the baroreceptor areas located within the carotid sinus and aortic arch regions (7). In the study reported here, since openchest dogs were used in all except two experiments, changes in arterial pressure resulting from changes in intrathoracic pressure were avoided.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Previous analysis has shown tliut lung inflation plays ati important part in modifying the cardiovascular response of the rahhit and of other species during strong clu-moreceptor stimulation. Thus, Daly et al (1967), Daly and Rohinson (1968) and Angel! James and Daly (1969) have shown in the dog that lung inflation inhibits the primary circulatory effects of strong ehemoreeeptor stimulation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is possible that whereas the respira tory reflex response is inhibited by facial receptors, the cardiac ren rx "is ér!nrtrî(":hcl n i " triril i Î wnrr -i n-r "i a -r n r-2 t : c cc 'r\\r na 1 /Hal \/ a w/n Scott; 1958; and vasodilation in the splanchnic vascular bed, skin, and muscle by reducing the activity of adrenergic sympathetic fibers (Daly et al, 1967). The receptors responsible for initiating these changes are the pulmonary stretch receptors (Daly and Robinson, 1968;Hainsworth et al.…”
Section: It Thus Seemed Likely That the Chemoreceptors Stimulated Bymentioning
confidence: 99%